1992
DOI: 10.1152/ajpgi.1992.262.2.g308
|View full text |Cite
|
Sign up to set email alerts
|

EndothelinB receptor on guinea pig small intestinal smooth muscle cells

Abstract: We investigated the binding characteristics of the endothelin (ET) receptor and the mechanism by which ET induces contraction of longitudinal smooth muscle cells of the guinea pig small intestine by using vasoactive intestinal contractor (VIC), a mouse variant of ET-2. A functional receptor for VIC was found to exist on longitudinal smooth muscle cells. These cells showed a similar binding of and contractile response to ET-1, ET-2, and ET-3. Inhibitors of both intracellular and extracellular Ca2+ movement atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…First, other functional and biochemical studies have shown that ETs can relax the intestine by a direct action on muscle cells. 9,13,15 Second, the antiperistaltic effect of ET-1, which is unmasked by BQ-123 and hexamethonium, seems to be mediated by ET B receptors that are situated beyond enteric pathways involving transmission via nicotinic acetylcholine receptors ( Figure 6). Third, the pharmacology of the properistaltic action of BQ-788 likewise points to a muscular location of the ET B receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, other functional and biochemical studies have shown that ETs can relax the intestine by a direct action on muscle cells. 9,13,15 Second, the antiperistaltic effect of ET-1, which is unmasked by BQ-123 and hexamethonium, seems to be mediated by ET B receptors that are situated beyond enteric pathways involving transmission via nicotinic acetylcholine receptors ( Figure 6). Third, the pharmacology of the properistaltic action of BQ-788 likewise points to a muscular location of the ET B receptors.…”
Section: Discussionmentioning
confidence: 99%
“…ET A and ET B receptors are present on neurons of the myenteric and submucosal nerve plexus, stromal cells of the mucosa, blood vessels, muscularis mucosae, and circular and longitudinal muscle layer. 1,2,7,9,10 The motor actions of ETs, which have been studied mostly in the guinea pig intestine, are complex and comprise both excitatory and inhibitory effects, depending on which receptors on enteric nerve or intestinal muscle are activated. [11][12][13] Collectively, it seems that ET-evoked muscle contraction is primarily mediated by ET A receptors, whereas ET-induced muscle relaxation is predominantly brought about by ET B receptors.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Both endothelin ETA and ETB receptors are present in intestinal smooth muscle cells and both may mediate contractions (Yoshinaga et al, 1992;Hori et al, 1994;Okabe et al, 1995;Smith et al, 1995). The endothelin ETB receptor has been postulated to participate partially in ET-induced relaxation of guinea-pig ileum (Hori et al, 1994), to be responsible for ion transport in rabbit colonic mucosa (Smith et al, 1995), and to play an essential role in the normal development of enteric ganglion neurones, based on the finding that a null mutation induced by targeted disruption of the mouse endothelin ETB receptor gene produced an aganglionic megacolon (Hosoda et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…83,223,224 My own opinion is that stimulation of ednrB in nonneural crest cells is not required for complete colonization, because selective expression of ednrB in the enteric neural precursors of transgenic mice is sufficient to compensate for deletions of the endogenous ednrB gene. 225…”
Section: A Successful Colonization Of the Gut By Enteric Neural Precmentioning
confidence: 99%